Proceedings of the International Conference on Ubiquitous Computing and Ambient Intelligence (UCAmI 2024) - Bravo, José; Nugent, Chris; Cleland, Ian (Lecture Notes in Networks and Systems, 2024)
XXIII, 957 p. 351 illus., 290 illus. in color.